2016
DOI: 10.3390/ijerph13040424
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depressive Symptoms and Related Factors in Korean Employees: The Third Korean Working Conditions Survey (2011)

Abstract: The aim of this study was to analyze the association between general working conditions and depressive symptoms among Korean employees. The target population of the study was native employees nationwide who were at least 15 years old, and 50,032 such individuals were enrolled in the study. Depressive symptoms was assessed using the WHO-5 wellbeing index. Associations between general characteristics, job-related characteristics, work environment, and depressive symptoms were tested using chi-square tests, t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
21
2
1
Order By: Relevance
“…Similarly, Driesen's prospective study indicated that depressed mood among shift workers non-significantly increased when adjusting for potential confounding factors, whereas retrospective analyses in their study found that former or current male shift workers had a statistically significant increased risk of depressed mood and depressive disorder (11). However, the remaining studies included in our analysis consistently revealed that night shift work was associated with the increased risk of depression (79101214151617). In the current meta-analysis, we were able to quantitatively suggest that night shift workers had an increased risk of depression by about 40%, compared with those without night shift.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, Driesen's prospective study indicated that depressed mood among shift workers non-significantly increased when adjusting for potential confounding factors, whereas retrospective analyses in their study found that former or current male shift workers had a statistically significant increased risk of depressed mood and depressive disorder (11). However, the remaining studies included in our analysis consistently revealed that night shift work was associated with the increased risk of depression (79101214151617). In the current meta-analysis, we were able to quantitatively suggest that night shift workers had an increased risk of depression by about 40%, compared with those without night shift.…”
Section: Discussionmentioning
confidence: 78%
“…In a study of 3,013 employees based in Incheon, Korea, 26.1% of males and 28.7% of females were categorized into the depression group based on having CES-D scores of 16 or higher (12). Likewise, in a study that examined 50,032 Korean employees in 2011, 39% of the entire group (40.7% of males and 36.5% of females) scored 12 points or lower on the WHO-5 Wellbeing Index (25). A study of 8,522 employees of 329 Korean companies found that 15.9% of the employees were depressed, based on having CES-D scores of 21 or higher (13).…”
Section: Discussionmentioning
confidence: 99%
“…To date this has not been taken into account in data analysis. Other limitations found in literature concerning this topic include small sample size, small periods of observation for the exposure and/or the Beltagy et al outcome, and the reliance on self-report only to measure the outcome (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%